Production of Carrot Ciam Noodle from Composite Flour (wheat flour-sweet potato starch- germinated soy flour) By Adding Carrot Juice and Thickeners - Melisa Halim; Elisa Julianti; Herla Rusmarilin (Universitas Sumatera Utara, 2014)
Wheat flour is used in making a variety of foods such as bread, cookies, and noodles because the wheat flour contains gluten that gives the chewy characteristics. Wheat as raw material of wheat flour is still imported, that can disrupt food security in Indonesia. One of the efforts to reduce the use of wheat flour is by diversification. The implementation was done in the manufacture of noodles by substituting some of the wheat flour with sweet potato starch and germinated soy flour and carrots. The aim of this research was to produce carrot ciam noodles with better nutritional value.The research was conducted in two phases. 1) The manufacture of composite flour. The flour was tested on protein content, fat content, moisture content, ash content, carbohydrate content, crude fiber content, amilograph with Brabender viscoanalizer, whiteness, water absorption, oil absorption and gelatinization temperature. 2) The manufacture of ciam noodles from composite flour with the addition of carrots and thickeners. Composite flour of phase 1 which has the best protein content and water absorption would be used in making ciam noodles. The texture, color (Hunter method), water absorption, cooking loss, protein content, fat content, moisture content, ash content, crude fiber content, carbohydrate content and organoleptic tests were tested on pre-cooked carrot ciam noodles, boiled and fried. The results showed that carrot ciam noodles made from 50% wheat flour, 25% sweet potato starch and 25% germinated soy flour with the addition of 20% carrots and 1% CMC produced the best carrot ciam noodles. Keywords: Carrot, ciam noodles, germinated soy flour, sweet potato starch.